Media and culture: modern challenges - Savinova , Olga N. (Journal of the Belarusian State University. Journalism, 2020)
The article discusses the controversial aspects of coverage of cultural issues in the media and the influence of the media on the modern sociocultural space. The author emphasizes that mass media undergo significant changes in the modern conditions of transformation of the society. Their role in the coverage of cultural issues is contradictory: there is a decrease in the quality of content, the processes of aberration of some functions (cultural, educational, information) are developing; entertainment function is hypertrophied. In pursuit of profit, media begin to construct ideals and values that are far from real life. The author also draws attention to such an urgent problem as the language of the media. In conditions when newspapers, radio and especially television have practically replaced the reading, media became the main sphere where the modern Russian language lives. That’s why the problem of the language of the media has global cultural and spiritual significance for society. The author emphasizes the necessity of increasing the role of the expert community as well as the audience itself in the formation of quality content related to the coverage of actual cultural issues. The author also focuses on the issues of media education and necessity to preserve the national traditions of Russian journalism, its high professional, intellectual  and cultural potential.
Keywords: culture; media; media transformation; media education; cultural competence of journalists